Some Pharmacological And Phytochemical Studies Of Clitoria Ternatea Extracts - Linggam, Kamilla (2012)
In this thesis, detailed work was carried out to explore and determine the phytochemical screening, potential anti-infective, antioxidant and analgesic properties of C. ternatea plant parts using various bioassays techniques and appropriate experimental models. The initial qualitative phytochemical screening shows that C. ternatea plant parts contain tannin, phlobatannin, flavonoid, anthraquinone, alkaloid, saponin, cardiac glycosides, volatile oils, steroids and terpenoids. The flavonoids and phenolic content of the various plant parts were also determined in the plant parts. Analysis shows that C. ternatea flower extract has both high phenolic (104.77 ± 2.64 mg GAE/g) and flavonoid (28.10 ± 4.13 mg CE/g) content than other plant parts. This is evident by the fact that C. ternatea flower extract exhibited the highest antioxidant activity (FRAP: 6.80 ± 0.32 μM Fe(II)/g ; DPPH IC50 : 9.17 ± 0.003 μg/mL) when compared to other parts of the plant. One of the bioactives identified in the flower extract was kaempferol-3-glucoside (K3G) which is a flavonoid compound. Kaempferol-3-glucoside was also found in C. ternatea stem and leaf. This could be one of the identified bioactives responsible for the antioxidant activity. As for the in vitro anti-infective screening, both leaf and root crude extracts demonstrated marked antimicrobial activities. Interestingly, the leaf extract demonstrated a remarkable antifungal activity against Aspergillus niger with a MIC and MFC of 0.4 and 0.8 mg/mL, respectively. This was evident by the scanning electron microscope (SEM) analysis which showed a marked morphological alteration of the A. niger hyphal wall and conidiophores after exposure to C. ternatea leaf extract when compared to control.